Optimization of four-Chamber and eccentric ellipse mufflers hybridized with multi-Segment perforated/non-perforated tubes - Min-Chie Chiu; Ying-Chun Chang; Ho-Chih Cheng (Journal of Low Frequency Noise, Vibration and Active Control, 2023)
Muffler with circular section and inner symmetric acoustical elements has been habitually used in industry. In order to improve the acoustical performance, an advanced eccentric muffler having ellipse cross-section, multiple chambers, and multi-segment perforated/non-perforated tubes is presented. Concerning about high order wave effect to the muffler, a finite element method (FEM) run on COMSOL package is adopted. In addition, the influence of sound transmission loss with respect to various geometric parameters has been explored. In order to simplify the optimization process, a simplified objective function established by an Artificial Neural Network (ANN) and FEM has been implemented and connected to a Genetic Algorithm (GA). Two case studies of muffler optimization for two kinds of design parameter sets (one of Lin and Lout and the other of Lin1 and Lout 1) are introduced. Two targeted frequencies (1000 Hz and 2500 Hz) are selected and applied in the two cases’ muffler optimization. Simulated results reveal that the acoustical influence relating to various geometric parameters is huge. The sound attenuation will increase in the low frequency region if the curvature ratio δ (ratio of long axis to short axis in ellipse) or the X (horizontal length of the muffler’s body) increases. Consequently, the study demonstrates a methodology in the optimization of a four-chamber ellipse and eccentric muffler internally inserted with multi-segment perforated/non-perforated tubes.